The Peshekhonovs' workshop : the heritage in icon painting - Belik, Zhanna (2008)
This thesis focuses on the activity of the St Petersburg icon painting workshop owned by the Peshekhonovs, and on the identification and investigation of the surviving icons created in this studio. The workshop was found by Makary Samsonovich Peshekhonov (1780-1852) in the 1820s. After his death the enterprise was led by his son Vasily Peshekhonov (1818-1888), who was granted the title of "Iconographer to the Imperial Court" in 1856. In published and archival sources, the Peshekhonov icons have been defined as paintings in the Byzantine, Greek or Ancient Russian style. The revival of the Byzantine tradition was a feature of Russian church art in the 1840 - 1880s. During this period a more scientific approach was taken to the restoration and conservation of original Byzantine and ancient Russian artworks. Furthermore, these decades witnessed the increasing study and classification of icons and manuscripts, along with research expeditions to the Russian provinces and to Ahos, with a view to investigating the ancient objects to be found in these places, and to undertaking the collection of antiquities. All of these internal processes stimulated a Byzantine style in church art. According to archival material, the Byzantine style in church paintings was interpreted via the Peshekhonov icons. In addition, the revival of the Byzantine tradition in church art became an important part of a state program promoting nationalism in the mid-19th century; there was a widespread notion of Russia as the heir to the Byzantine Empire, a concept that was also reflected in international policy. The Peshekhonovs combined medieval iconography and an academic manner of creating art. The workshop employed mixed techniques of icon painting, with golden embossment and a wealth of decoration. The techniques and technology utilized by the Peshekhonov workshop are described in detail in the second chapter of this thesis. The Peshekhonov icons identified are divided into two groups: signed and unsigned. The identification of unsigned icons is based on an analysis of the signed icons and of archival materials, and on comparative characteristics. During the research for this thesis, over 120 Peshekhonov icons were identified in Finland, Russia, Israel, Latvia, Ukraine, and Europe. The Peshekhonovs established a special design style of icon painting – the "Peshekhonov style" - which had a strong influence on the visual characteristics of the icons painted in 1840-1880, within St Petersburg and the Russian provinces.